Clinical characteristics and long-term prognosis of female patients with acute coronary syndrome - Rocamora-Horrach, Mar; Peiró, Óscar M.; Bardají, Alfredo; Flores-Benítez, Javier; Ivorra-Cámara, Miguel; Carrasquer, Anna; Ferreiro, José Luis (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiovascular disease has traditionally been studied predominantly in men, but understanding its manifestations in women is crucial for effective management. This study aims to evaluate the long-term prognosis of female sex in acute coronary syndrome (ACS) within a tertiary hospital setting in Spain. Methods: Retrospective observational study based in a cohort of consecutive hospitalized patients with ACS from January 2009 to December 2014. Data on demographics, risk factors, treatment, and outcomes were collected, with a median follow-up of 9.2 years. Results: Women with ACS, constituting 27.3% of 2,330 patients, were older and had higher prevalence of cardiovascular risk factors such as obesity, hypertension, and diabetes mellitus compared to men. They presented with more non-ST-segment elevation myocardial infarction and underwent less coronary angiography. Female sex was also less likely to be treated with acetylsalicylic acid, a second antiplatelet drug, or statins. Despite initial higher mortality rates (HR 1.30; 95% CI 1.13 -1.49; p<0.001), female sex exhibited a more favorable long-term prognosis after adjustments (adjusted HR 0.82; 95% CI 0.71 -0.96; p = 0.014), even in the subgroup analysis excluding patients with unstable angina. Conclusions: Women with ACS are more comorbid, but after adjustments female sex appears to be a protective factor that confers a better long-term prognosis.